How are links between a National Qualifications Framework, job roles and pay mediated by industrial relations institutions in manufacturing? - Oliver, Damian [Verfasser]; Walpole, Kurt [Verfasser] (My University, 2017)
"National Qualifications Frameworks (NQFs) are intended to promote stronger linkages between education institutions and the labour market. This paper examines how industrial relations institutions mediate the relationship between formal qualifications, job classifications and pay outcomes in Australian manufacturing. In Australia a tribunal sets job classifications and pay grades through industry-based awards; collective agreements that displace the award can be negotiated, primarily on an enterprise by enterprise basis. In a representative sample of 100 collective agreements in the manufacturing industry, we find linkages in collective agreements are less common, weaker and refer to a narrower range of qualifications than the comparable awards. In fact, a third of enterprise-level collective agreements contain no reference at all to an NQF qualification. These findings suggest that diffusion of NQFs in the labour market cannot be taken for granted and challenge prescriptions that qualifications should be defined around narrow descriptions of competence to reflect employer preferences." (author's abstract ; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.3.3.1 Qualifikationsverwertung; I 2.3.5 Australien, Ozeanien; Nationaler Qualifikationsrahmen; Beziehung Bildungssystem Beschäftigungssystem; Berufliche Qualifikation; Bildungsabschluss; Lohn; Australien